Melanchra postalba Sugi 1982 - Rybalkin, S. A.; Yakovlev, R. V.; Benedek, B. (Zenodo, 2018)
Melanchra postalba Sugi, 1982 Fig. 5 MATERIAL. Russia : Sakhalin Island, Korsakovo distr., 10 km NW Lesnoe, Dolinka river, 5‒6.VIII 2015, 2 ♂, leg. S. Rybalkin. DISTRIBUTION. Japan, Korea, China, Russia (Primorskii krai) (Anikin et al ., 2016). Here this species is firstly recorded from Sakhalin Islands. Published as part of Rybalkin, S. A., Yakovlev, R. V. & Benedek, B., 2018, New and little known for the fauna of Kunashir and Sakhalin Islands Lasiocampidae and Noctuoidea (Lepidoptera), pp. 18-22 in Far Eastern Entomologist 355 on page 21, DOI:10.25221/fee.355.3, http://zenodo.org/record/7164421